George Washington Paschal, A Digest of the Laws of Texas: Containing Laws in Force, and the Repealed Laws on Which Rights Rest Page, at 1321-22, An Act to Prohibit the Carrying of Firearms on Premises or Plantations of Any Citizen Without the Consent of the Owner, Art. 6510. (Vol. 2, 1873) - (:unkn) unknown (My University, 1873)
It shall not be lawful for any person or persons to carry firearms on the enclosed premises or plantation of any citizen, without the consent of the owner or proprietor, other than in the lawful discharge of a civil or military duty, and any person or persons so offending shall be fined a sum not less than one nor more than ten dollars, or imprisonment in the county jail not less than ten days, or both, in the discretion of the court or jury before whom the trial is had.
Keywords: CARRY